Application of The Law and The Implications of Imposing Chemical Castration in Judgment No. 895/Pid.Sus/2023/Pn.Bjm From The Perspective of Legal Positivism - Wahyu Kurniawan; Ulfia Pamujiningsih (UIN Mahmud Yunus Batusangkar, 2026)
The phenomenon of implementing chemical castration as an additional penalty in the Banjarmasin District Court Decision Number 859/Pid.Sus/2023/PN Bjm has sparked serious debate within the realm of criminal law, particularly when examined through the perspective of legal positivism, which emphasizes the supremacy of written norms over moral and social considerations. Utilizing a normative juridical approach through case and statute analysis, this study examines the consistency of legal application by judges in sentencing perpetrators of sexual violence against children. The results of the analysis indicate that while the application of Article 81 paragraph (3) of Law Number 17 of 2016 was appropriate for the principal penalty, the imposition of chemical castration lacked a valid legal basis as stipulated in Article 81 paragraphs (4) and (5). This discrepancy poses significant issues regarding the principle of legality, legal certainty, and the protection of human rights. Conceptually, these findings affirm that a rigid application of legal positivism has the potential to obscure substantive justice values, which should serve as the essence of every judicial decision.